ICT adoption among SME entrepreneurs in the furniture industry / Chin Tee Suan...[et al.] - Suan, Chin Tee; Raman, Kavitha; Ai, Yeow Jian; Cuang, Lee Siau; Wei Loon, Koe (PENERBIT PRESS Universiti Teknologi Mara, 2012)
Information and communication technology (ICT) plays a vital role especially in supporting process innovation, in manufacturing as well as in the service industries. This can be confirmed for the furniture sector. Appropriate ICT can help firms reduce costs by enhancing their internal processes, improving their product and distributing their products. In Malaysia, furniture industry has become one of the country's most economically important sectors. The total value of furniture products export of Malaysia has increased gradually from in 2003 to 2007. This sector is dominated by small and medium sized enterprises. About 2000 companies are involved in the furniture industry belonged to the SMEs. The objective of this study is to examine the adoption rate of ICT among the SME entrepreneurs in the furniture industry. It was found that a majority of the companies surveyed did use computers but their usage is very basic. They are not fully utilising the capabilities of ICT.